Consent approaches for research into intrapartum complications: a systematic review. (7th June 2011) - Nasir, S A; Patel, D; Elati, A; Weeks, A; Vernon, G
Abstract : Objective: To review the consent approaches that researchers have used for trials conducted between the 1950s and 2000s concerning intrapartum complications. Method: The Cochrane Library database was used to access intrapartum trials related to the management of complications during labour. Studies excluded from analysis were abstracts, non-English, non-RCTs, prophylactic studies, repeat publications of a single RCT, unpublished trials and those investigating non-obstetric complications. Results: 138 studies met the inclusion criteria. Seeking consent at the time of complication was the most common approach. It constitutes 58% of the first stage and 41% of the second stage labour trials. In contrast, obtaining consent from total population during early labour was the most common approach in third stage trials (26%). Overall, researchers did not report taking consent in 20% of the first stage trials, 48% in the second stage and 30% in the third stage of labour trials. Between 1950s and 1970s, 100% of studies had no evidence of consent recorded. Consent at the time of complication was the most popular approach in the 1990s (66%). Throughout 2000–2010, 20% of researchers sought consent from the total population during early labour and 18% provided antenatal information and then obtained consent at the time of complication. Conclusion: Over the last three decades, researchers have been getting better at seeking consent by using a variety of different consent approaches. Labouring women should be considered as a special group of subjects, the physical and psychological effects of labour make this group vulnerable.